2005
DOI: 10.1016/j.pharmthera.2004.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Current topics of physiology and pharmacology in the lymphatic system

Abstract: We have reviewed physiological significance of rhythmical spontaneous contractions of collecting lymph vessels, which play a pivotal role in lymph transport and seem to control lymph formation through changing the pacemaker sites of the rhythmic contractions and contractile patterns of the lymphangions. A characteristic feature that the rhythmic pump activity works in vivo physiologically under the specific environment of lower oxygen tension in lymph (25-40 mm Hg) has been evaluated. With the characteristic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
87
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 129 publications
2
87
0
Order By: Relevance
“…NO regulates the vasomotor activity of lymphatic microvessels, 8,28 inducing dilation, and it may act as a lymphangiogenetic factor through interaction with VEGF-C, as previously demonstrated in breast cancer and head and neck squamous cell carcinomas. 5,29 Interestingly, VEGF-C-overexpressing melanomas showed enhanced tumor angiogenesis, suggesting a coordinated 30,31 CD105 is an endothelial marker that reacts uniquely with endothelial cells of newly formed vessels, and, specifically of immature tumor blood vessels.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…NO regulates the vasomotor activity of lymphatic microvessels, 8,28 inducing dilation, and it may act as a lymphangiogenetic factor through interaction with VEGF-C, as previously demonstrated in breast cancer and head and neck squamous cell carcinomas. 5,29 Interestingly, VEGF-C-overexpressing melanomas showed enhanced tumor angiogenesis, suggesting a coordinated 30,31 CD105 is an endothelial marker that reacts uniquely with endothelial cells of newly formed vessels, and, specifically of immature tumor blood vessels.…”
Section: Discussionmentioning
confidence: 54%
“…[2][3][4][5] Tumor-cell-derived NO has been proposed to be an important mediator of tumor angiogenesis and metastasis formation by directly inducing vessel dilation, promotion of blood flow and vascular permeability and endothelial cell proliferation through upregulation of vascular endothelial growth factor (VEGF) and basic fibroblastic growth factor. 6,7 In addition, more recent observations indicate that NO is involved in the regulation of lymphatic vessels permeability and flow 8 and we have recently demonstrated that iNOS activity correlated with lymphangiogenesis and spread to lymph nodes in head and neck squamous cell carcinoma. 5 It is possible that in the tumor microenvironment NO stimulates angiogenesis and/or lymphangiogenesis cooperatively with other proangiogenic and lymphangiogenic growth factors.…”
mentioning
confidence: 96%
“…Collecting lymphatic vessels can produce flow autonomously using smooth muscle cell (SMC)-driven contractions, which drive flow through one-way intraluminal valves and lymph nodes before its return to the blood circulation (10). Although studies of lymphatic pumping in large animals have given insights into lymphatic contraction (11)(12)(13)(14)(15), molecular control of this process is not well understood. Given the ready availability of molecular reagents, genetic knockouts, and disease models in mice, an in vivo murine model of lymphatic contraction will advance the field by dissecting the underlying molecular mechanisms under normal and pathological conditions.…”
mentioning
confidence: 99%
“…Several studies have shown the involvement of the lymphatic endothelium in the NO-mediated modulation of lymphatic contractile activity. 11,[14][15][16] In particular, specific immunostaining of endothelial nitric oxide synthase (eNOS) was demonstrated in endothelial cells of bovine lymphatics 17 and in rat lymphatic endothelial cells. 18 In functional experiments it was demonstrated that precontracted dog thoracic duct rings relaxed to acetylcholine (ACh) or sodium nitroprusside (SNP).…”
mentioning
confidence: 99%
“…Because of the importance of the NO molecule released by lymphatic endothelium for the regulation of lymphatic contractility and flow in adult 11,14,16,27,[32][33][34] and aged 4,24,29 lymphatic vessels, in the discussed study 30 we implemented in vivo the local NOS blockade induced by topical administration of 100 lM of L-NAME. We compared the contractile behavior of MLV and lymph flow in adult and aged groups before and after the L-NAME administration.…”
mentioning
confidence: 99%